An outbreak of chlamydiosis in captive blue-fronted Amazon parrots (Amazona aestiva) in Brazil - De Freitas Raso, Tânia [UNESP]; Godoy, Sílvia Nery; Milanelo, Liliane; De Souza, Cláudia Almeida Igayara; Matuschima, Eliana Reiko; Araújo Jr., João Pessoa [UNESP]; Pinto, Aramis Augusto [UNESP] (American Association of Zoo Veterinarians, 2004)
Fifty-eight blue-fronted Amazon parrot (Amazona aestiva) nestlings, recovered from the illegal trade, became ill at a wildlife rehabilitation center in São Paulo State, Brazil. Clinical signs observed were nonspecific, and the mortality rate was 96.5% despite initial treatment with norfloxacin. Postmortem examinations were performed on 10 birds. Liver and spleen smears showed structures suggestive of Chlamydophila psittaci in four cases. Diagnosis was confirmed by seminested polymerase chain reaction on tissue samples. Other birds from the same location showed no clinical signs of the disease, although high complement fixation titers to C. psittaci were found in 10 adult psittacines. All birds in the facility were treated with doxycycline. The two surviving nestlings did not recover after two doxycycline treatments and were euthanatized. The high mortality rate observed in this outbreak was attributed to poor conditions of husbandry and delays in the diagnosis and treatment of the disease. After diagnosis, improved control measures for chlamydiosis were instituted.
Keywords: Amazona aestiva; Blue-fronted Amazon parrot; Brazil; Chlamydiosis; Chlamydophila psittaci; antiinfective agent; doxycycline; animal; animal disease; animal husbandry; bird disease; case report; epidemic; female; isolation and purification; male; methodology; microbiology; mortality; ornithosis; parrot; pathogenicity; time; Animal Husbandry; Animals; Anti-Bacterial Agents; Bird Diseases; Disease Outbreaks; Doxycycline; Female; Male; Parrots; Psittacosis; Time Factors; Amazona; Animalia; Aves; Psittacidae